2020
DOI: 10.1017/ice.2019.373
|View full text |Cite
|
Sign up to set email alerts
|

Considerable variability in antibiotic use among US children’s hospitals in 2017–2018

Abstract: Objective:To characterize the prevalence of and seasonal and regional variation in inpatient antibiotic use among hospitalized US children in 2017–2018.Design:We conducted a cross-sectional examination of hospitalized children. The assessments were conducted on a single day in spring (May 3, 2017), summer (August 2, 2017), fall (October 25, 2017), and winter (January 31, 2018). The main outcome of interest was receipt of an antibiotic on the study day.Setting:The study included 51 freestanding US children’s ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Previous studies reported that 60% of all inpatients received antibiotic medications in 2008, 21 whereas 36% of inpatients received an antibiotic medication in 2017. 22 The use of chest radiography has also been reported to be decreasing among children with respiratory illness, 23 which was consistent with our results. Notably, although previous work has revealed increasing use of ECMO in adults with influenza, 24 we did not find increases in ECMO use among children.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies reported that 60% of all inpatients received antibiotic medications in 2008, 21 whereas 36% of inpatients received an antibiotic medication in 2017. 22 The use of chest radiography has also been reported to be decreasing among children with respiratory illness, 23 which was consistent with our results. Notably, although previous work has revealed increasing use of ECMO in adults with influenza, 24 we did not find increases in ECMO use among children.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, even after controlling for region and many other patient and hospital characteristics, we found that a patient’s probability of receiving broad-spectrum empiric therapy could still be twice that of an otherwise equal patient, due solely to their different admitting hospitals. High, unexplained interhospital variability has also been documented for empiric therapy [ 49 ], broad-spectrum therapy [ 50 ], and total antibiotic usage [ 51 ] across US pediatric hospitals. Taken together, these findings—empiric antibiotic usage as a possible correlate of total antibiotic usage and existing high random variability—suggest that the empiric window is an underexploited but potentially “high-yield” target for antibiotic stewardship efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic and broad-spectrum antibiotics were defined as previously published (Table 1). 6 We reported antibiotic use according to patient characteristics including age, gestational age at birth, sex, race or ethnicity, and service line (medical or surgical) as determined by all patient-refined diagnosis-related group (APR-DRG, version 32, 3M, Maplewood, MN). Differences between groups were measured using the χ 2 test or the Fisher exact test.…”
Section: Methodsmentioning
confidence: 99%
“…Hospital characteristics included geographic census region and case mix index (CMI), a surrogate for illness severity. 6 We calculated the prevalence of antibiotic use by dividing the number of patients who received at least 1 antibiotic (or 1 broad-spectrum antibiotic) by the number of patients hospitalized in NICUs on the study day. We also measured the association between NICU antibiotic use prevalence and median hospital CMI using the Pearson correlation.…”
Section: Methodsmentioning
confidence: 99%